The burden of polycystic ovary syndrome-related infertility in 204 countries and territories, 1990-2021: an analysis of the global burden of disease study 2021 - Zheng, Lan; Xu, Xiao; Zhou, Jin-Zhuo; Hong, Lin; He, Yu-Feng; Fang, Ya-Xing; Wang, Bing-Bing; Chen, Hui; Chen, Kang-Jia; Yang, Su-Su; Yang, Xiao-Long; Pan, Hai-Feng; et al. (Frontiers in Endocrinology, 2025)
ObjectivesThe evolving patterns of the infertility attributed to polycystic ovary syndrome (PCOS) disease burden are being evaluated, stratified by age, region, subtype, and health condition.Material and methodsThis cross-sectional investigation encompassed data from 21 regions and 204 countries from 1990 to 2021, sourced through the Institute for Health Metrics and Evaluation. The prevalence and YLDs due to infertility, overall and stratified by age, subtype, region, country, and health status. The percent change in age-standardized rates (ASR) was calculated to temporal quantify the trend of infertility burden. The Bayesian age-period-cohort (BAPC) model was employed to forecast the trends in the ASR of prevalence and YLD from 2022 to 2042.ResultsGlobally, the age-standardized prevalence and YLDs in infertility attributed to PCOS showed a significant increase trend from 1990 to 2021, with ASR of 34.2% (95%CI: 28.2 to 41.5%) and 32.5% (95%CI: 26.6 to 39.4%), respectively. The spatiotemporal trends in infertility attributed to PCOS varied substantially between subtypes and age groups. The burden of primary infertility peaked among individuals aged 20 to 24 years, whereas secondary infertility consistently peaked among individuals aged 35 to 44 years. The BAPC model showed that the burden of infertility will increase over the next 2 decades.ConclusionsInfertility attributed to PCOS remains to be a significant public health issue globally, with this burden varying considerably across age groups, and subtypes. Decision-makers providers must take a proactive stance in monitoring developing trends and adapting infertility screening and management protocols to different age brackets and subtypes.